Analisis rendahnya kemampuan membaca peserta didik kelas IV di SD Negeri 01 Bali Agung - Wahyuni, Ida; Shalsabila, Adella; Ningrum, Sekar Tyas Ayu; Darsono, Darsono (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
The phenomenon of low reading ability of fourth grade elementary school students is the main focus of this study. The purpose of this study is to analyze the low reading ability of fourth grade students of SD Negeri 01 Bali Agung. The method in this study uses a qualitative approach through case studies or problems. Data collection techniques in this study were through in-depth interviews with teachers, and direct observation of the learning process in the classroom. The results obtained from this study are that low reading ability can be caused by two factors, namely internal factors and external factors.